Modeling of a Tubular Fixed-Bed Reactor for the Production of Dimethyl Ether Using Alumina Catalyst - Kekpugile, Dagde Kenneth; Sylvanus, Harry Uduak (International Journal of Chemical and Process Engineering Research, 2016)
A model to predict the behavior of an adiabatic tubular fixed-bed reactor for the production of dimethyl ether using alumina catalyst was developed. The steady state model incorporates the reaction rate kinetic expression obtained from literature into the model equations. The models were integrated numerically using Fourth-order Runge-Kutta method incorporated into a computer simulator (MATLAB 7.7 code). Model predictions are compared with data obtained from the literature under the same operating conditions and a good agreement is obtained with a variation ranging from 0.5% to 2.7%. The simulation results show that the production of dimethyl ether is greatly affected by parameters such as temperature, and feed flow rate with optimum yield of DME at a catalyst bed height of 2-4m at a temperature of 557 to 570K.